Clinical nursing and midwifery education in the pandemic age. (23rd June 2020) - Lazenby, M.; Chambers, S.; Chyun, D.; Davidson, P.; Dithole, K.; Norman, I.; Tlou, S.
Abstract : The COVID‐19 pandemic has disrupted clinical nursing and midwifery education. This disruption has long‐term implications for the nursing and midwifery workforce and for future healthcare responses to pandemics. Solutions may include enhanced partnerships between schools of nursing and midwifery and health service providers and including schools of nursing and midwifery in preparedness planning. These suggestions notwithstanding, we call upon national and international nursing and midwifery bodies to study how to further the clinical education of nurses and midwives during pandemics and other times of crisis.